Enhanced Thermal and Electrical Properties of Polystyrene-Graphene Nanofibers via Electrospinning. (10th October 2016) - Li, Yan; Porwal, Harshit; Huang, Zhaohui; Zhang, Han; Bilotti, Emiliano; Peijs, Ton
Abstract : Polystyrene- (PS-) graphene nanoplatelets (GNP) (0.1, 1, and 10 wt.%) nanofibers were successfully produced via electrospining of dimethyformamide- (DMF-) stabilized GNP and PS solutions. Morphological analysis of the composite nanofibers confirmed uniform fiber formation and good GNP dispersion/distribution within the PS matrix. The good physical properties of GNP produced by liquid exfoliation were transferred to the PS nanofibers. GNP modified PS nanofibers showed a 6-fold increase in the thermal conductivity and an increase of 7-8 orders of magnitude in electrical conductivity of the nanofibers at 10 wt.% GNP loading.